Implementing the Authority of the State’s Attorney in Legal Assistance in Handling Covid-19 in Denpasar City - I Nyoman Budiana; Leo Liusiana (Fakultas Hukum, Universitas Warmadewa, 2023)
The emergence of a disease outbreak, namely Corona Virus Disease 2019 (Covid-19) in most countries in the world, has caused various problems, not only in the health sector but also in the economic, political and socio-cultural fields. This study aims to analyze the attorney’s authority in providing legal assistance and examine various factors that support and hinder the handling of Covid 19 in Denpasar City. The research design used is a normative juridical approach with a statutory law approach, an analytical and conceptual approach and several facts collected from informants as support and qualitative descriptive juridical analysis was used to obtain adequate and accurate results. The result shows that the implementation of legal assistance to policies in the framework of accelerating the handling of Covid 19 and the National Economic Recovery program by the State’s Attorney of Denpasar District Attorney was carried out well and effectively. The factors that support the implementation of the legal assistance are the clarity of the legal basis used by the prosecutor’s office in carrying out its functions and the fast and active response from the applicant, namely some agencies in Denpasar City. While the inhibiting factors include the reporting process provided by the applicant to the attorney’s office is still slow, the limited number of members of the State’s Attorney with authority as public prosecutors must continue to be carried out within the framework of law enforcement.